Association between prolonged QTc interval and microalbuminuria in patients of Type II diabetes mellitus - DR.S.SAKTHI SELVA KUMAR; DR.SANDHYA; DR.PALANIANDAVAN (International Journal of Pharma and Bio Sciences, 2017)
Autonomic neuropathy and nephropathy are common but severe complications of diabetes. QTc prolongation is a predictor of CAN (Cardiac autonomic neuropathy) and microalbuminuria is a predictor of nephropathy. This study was done to find the association between QTc interval prolongation and microalbuminuria in patients of type II diabetes mellitus. This cross sectional study was conducted in sree balaji medical college and hospital with 60 patients of type 2 diabetes mellitus. A complete History and thorough clinical examination were recorded in these patients at the time of admission. All these patients were tested for microalbuminuria and QTc interval prolongation in ECG. Study analysed by chi square test from two sample proportion. Most of the patients were in 50 to 70 years of age group. There is a significant association between QTc prolongation and microalbuminuria as evidenced by (67.76% Vs 24.13%, P<0.0001) more number of cases with microalbuminuria having prolonged QTc interval. Male to female ratio is 1.15:1. In addition to this it was noted that there is increase in incidence of QTc interval prolongation and microalbuminuria as the duration of diabetes increased. There was a significant association between cardiac autonomic neuropathy (i.e. QTc prolongation) and microalbuminuria. Microalbuminuria doesn’t directly cause QTc prolongation but it can be used as an indicator for patients who are prone to develop cardiac autonomic neuropathy and hence are at higher risk of having fatal arrhythmias.